Diversity and Similarity of Flatfishes (Order- Pleuronectiformes) in Mon State, Myanmar - Thet Htwe Aung; Mi Mi Latt; Yin Nwe Oo (International Marine Science Journal, 2019)
The samples of flatfishes were collected along the Mon State from July to December 2017 including Mawlamyine, Kyaikkhami, Setse, Zee-Phyu-Thaung Belugyun island, Paung and Thaton. The total 21 species of flatfishes were recorded in Mon State. Moreover, the relative abundance, diversity and similarity were conducted using Simpson Index, Shannon index and Jacquard’s index etc. According to the present study, the Cynoglossidae was the most dominant family and the most dominant species was Cynoglossusarelfor the present study. The relative abundance of Mawlamyine and November was relatively the highest. Furthermore, Mawlamyine was the highest diversity and Thaton was the lowest diversity. The JI value between Mawlamyine and Paung is the highest while it is the lowest between Setse and Thaton. Likewise, the JI value between August and September and the value between September and November are the same as well as the highest while it is the lowest for the comparison between July and August. The present study also expects to become a basic informational providing data for further observing (in Academic) on Order Pleuronectiformes (flatfishes) along the Mon State.
Keywords: flatfishes